Mortar Composition for Sound Attenuation and Fire Protection - Patent application

By using a cement composition containing a specific proportion of heavy гід binder, lightweight polymer, high-density polymer and polymer, the problem that acoustic barrier and fire resistance functions in the prior art is difficult to achieve simultaneously, and efficient acoustic barrier and fire resistance are achieved, which is suitable for a variety of industrial applications.

JP7662530B2Active Publication Date: 2025-04-15SIKA TECH AG
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
JP2021557017
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-06
Filing Date
2020-05-06
Publication Date
2025-04-15
Estimated Expiration
2040-05-06

AI Technical Summary

Technical Problem

It is difficult for the prior art to realize both acoustic barrier and fire protection functions at the same time. Especially in metal structures such as ships and automobiles, traditional acoustic barrier systems and fire protection systems need to be installed separately, and there are problems such as inconvenience in use and high cost.

Method used

A cement composition containing 15-50% weight binder, 5-35% lightweight polymer, 5-25% high density polymer and 10-50% polymer is used, which can produce a structure with acoustic barrier and fire-repellent functions without the use of isocyanates or corrosive substances.

Benefits of technology

It realizes acoustic barrier and fire protection functions in the same system, improves the acoustic barrier effect and fire protection performance, and has a simple and safe process, suitable for automobiles, ships, and construction fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662530000003
    Figure 0007662530000003
  • Figure 0007662530000004
    Figure 0007662530000004
  • Figure 0007662530000005
    Figure 0007662530000005
Patent Text Reader

Abstract

The present invention provides a mortar composition, in particular for preparing a viscoelastic structure and / or a fire barrier, comprising or consisting of: (a) 15 to 50% by weight of a hydraulic binder; (b) 5 to 35% by weight of a lightweight aggregate; (c) 5 to 25% by weight of a further aggregate having a particle density higher than that of the lightweight aggregate; and (d) 10 to 50% by weight of a polymer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a mortar composition, in particular for preparing a viscoelastic body or a structure and / or a fire barrier. Another object of the present invention is a molded body comprising the mortar composition after hardening with water, and a structure, in particular a floor, wall or ceiling, comprising the molded body. Furthermore, the present invention relates to the use of the mortar composition, the molded body and the structure. [Background technology]

[0002] In vehicles, buildings, or offshore facilities, the propagation of unwanted sound or vibrations through structural elements, floors, walls, or ceilings is a difficult problem. This is especially true in metal-based structures with large flat areas, such as automobiles, ships, and offshore facilities.

[0003] As a result, flat surfaces such as floors, as well as being smooth and flat, are expected to play a major role in noise and vibration suppression. On the ship's side, there are several major sound and vibration sources, such as diesel engines, gearboxes and propellers, which emit acoustic energy. In the field of sound and vibration engineering, the energy released by these sources is defined in two ways: Vibration: Dynamic fluctuations in solids and liquids · Sound: Fluctuations in air pressure in the audible frequency range (20Hz-20kHz).

[0004] For ships, the most primary propagation of unwanted sounds and noise is through the ship's structure. Engines, propellers, gearboxes, etc. each generate energy waves that emanate as structure-borne noise into the air from large flat areas, e.g. decks and bulkheads, which act as sounding boards.

[0005] Airborne noise is less prevalent as sound is carried laterally along entrance stairs and through partitions and bulkheads, decreasing substantially with distance from the source.

[0006] To reduce vibration and noise, viscoelastic damping systems can be applied directly onto the vibrating area or surface. These systems reduce the radiation of low frequency noise and dissipate acoustic energy into heat.

[0007] Several viscoelastic damping systems are commercially available. Highly efficient systems consist of a thin two-component polyurethane layer placed directly on the support surface to be damped (e.g. a deck surface made of steel or aluminum) and a restraining layer (e.g. a mortar-based layer or a steel tile) placed on top of the polyurethane layer. Within this system, the polyurethane layer functions as a viscoelastic damping element as well as a primer between the metal surface and the restraining layer. Although such viscoelastic damping systems have a significant damping effect, the polyurethane layer may not always be suitable for certain applications.

[0008] Furthermore, WO 2014 / 016131 A1 (Sika Technology AG) describes a mortar composition for preparing viscoelastic structures. The mortar composition is based on a hydraulic binder, aggregates, polymers and layered materials. The viscoelastic structures thus produced can be used as a replacement for known polyurethane systems.

[0009] In addition to vibration and sound damping in vehicles, buildings, or offshore facilities, another important aspect is the prevention of fire spread. Typically, this is achieved by (i) passive fire protection, such as the installation of fire barriers and fire rated floor assemblies to form fire compartments intended to limit the spread of fire, high temperatures, and smoke, or (ii) active fire protection, such as manual and automatic detection and suppression of fire using fire sprinkler systems and / or alarm systems.

[0010] In this regard, WO 2009 / 134299 A2 (Kaneka Corporation) describes a fire barrier system comprising flexible graphite sheets, suitable for installation on aircraft, ships or offshore platforms. Although such fire barriers are effective, they need to be installed in addition to vibration and sound damping systems.

[0011] Therefore, there remains a need to develop an improved system that provides sound attenuation and / or prevention of fire spread and overcomes the aforementioned drawbacks. Summary of the Invention [Problem to be solved by the invention]

[0012] It is an object of the present invention to provide a composition which allows the production of an acoustic damping element. In particular, the damping element should absorb noise in the audible frequency range, in particular in the frequency range from 50 to 5,000 Hz. In addition, the composition should preferably allow the production of an acoustic damping element with fire barrier properties.

[0013] The composition or the damping element, respectively, should be particularly suitable for marine and / or automotive applications. Moreover, the composition should preferably be free of isocyanates and corrosive compounds. Preferably, the composition or the damping element, respectively, should also have good adhesion to different types of materials, in particular to mortar, concrete and metals, such as steel, aluminum and zinc. Moreover, the damping element should be safe and easy to manufacture and use. The composition used to manufacture the damping element should also preferably be applied using standard equipment. [Means for solving the problem]

[0014] Surprisingly, it has been found that these objects are achieved by the features of claim 1. The core of the invention therefore comprises a mortar composition, in particular for preparing a viscoelastic structure and / or an acoustic damping element and / or a fire barrier, comprising: (a) 15 to 50 weight percent of a hydraulic binder; (b) 5 to 35% by weight of lightweight aggregate; (c) 5 to 25 weight percent of an additional aggregate having a particle density higher than the particle density of the lightweight aggregate; (d) 10 to 50% by weight of at least one polymer A mortar composition comprising or consisting essentially of:

[0015] Such mortar compositions can be used to produce advantageous viscoelastic structures or sound damping elements capable of absorbing noise in the frequency range of 50-5,000 Hz, for example in automotive and marine applications, without the need for any isocyanate-based materials or corrosive compounds.

[0016] The production of such elements or structures is very easy and safe: the mortar composition is mixed with the appropriate amount of water, especially in the dry state. After hardening of the mortar composition, the viscoelastic structure or the acoustic damping element is ready. Moreover, the mortar composition can itself be a one-component mixture. This would eliminate the risk of mix-up or incorrect dosing of the individual components by the user.

[0017] Furthermore, the mortar compositions of the present invention can be formulated so that they harden and dry rather quickly, especially when Portland cement is used in combination with aluminate and / or sulfoaluminate cements as hydraulic binders. Such types of compositions are particularly suitable for use with low-adsorption and non-adsorption substrates, such as substrates made of metal.

[0018] As can be shown, the mortar composition or the viscoelastic structure made therefrom is characterized by good adhesion to different kinds of materials, in particular to mortar, concrete and metals such as steel, aluminum and zinc. Therefore, the viscoelastic structure or the acoustic damping element made from the mortar composition of the invention is very compatible with elements of existing damping systems, such as for example existing containment layers.

[0019] Surprisingly, the mortar composition of the present invention shows rather strong adhesion to metal substrates even without the need for a primer. Therefore, the composition is particularly useful for application on structural elements made of metal in vehicles, buildings and offshore facilities.

[0020] Furthermore, the compositions of the present invention are highly suitable as passive fire protection systems, for example as fire barriers to limit the spread of fire.

[0021] Further aspects of the invention are the subject matter of further independent claims. Particularly preferred embodiments are outlined throughout the description and the dependent claims.

[0022] (Mode for carrying out the invention) A first aspect of the invention relates to a mortar composition, in particular for preparing a viscoelastic structure and / or an acoustic damping element and / or a fire barrier, comprising: (a) 15 to 50 weight percent of a hydraulic binder; (b) 5 to 35% by weight of lightweight aggregate; (c) 5 to 25 weight percent of an additional aggregate having a particle density higher than the particle density of the lightweight aggregate; (d) 10 to 50% by weight of at least one polymer The present invention is directed to a mortar composition comprising or consisting essentially of:

[0023] In particular, all amounts are based on the total weight of the mortar composition in the dry state.

[0024] In this context, the expression "hydraulic binder" denotes a substance that hardens in particular by chemical reaction with water to form hydrates. Preferably, the hydrates formed are not water-soluble. In particular, the chemical reaction of the hydraulic binder with water occurs essentially independently of the water content. This means that the hydraulic binder hardens and is able to retain its strength even when exposed to water, for example under water or under high humidity conditions.

[0025] The term "lightweight aggregate" refers in particular to aggregates up to 2,000 kg / m 3 Less than or equal to 1,500 kg / m 3 Below, especially 1,250 kg / m 3 The following particle densities of aggregates are represented. The particle density of aggregates is the ratio between the mass of the particulate material and the volume occupied by the individual particles. This volume includes the pores within the particles but does not include the voids between the particles. In particular, the particles of aggregates can have any spherical and / or non-spherical geometric shape, either uniform or non-uniform. For example, the particles can be spherical, conical, polygonal, cubic, pentagonal, hexagonal, octagonal, prism and / or polyhedral in shape. Non-uniform particles can have, for example, circular, elliptical, ovoid, square, rectangular, triangular or polygonal cross sections found at least partially therein. "Non-uniform" and "irregular" shaped particles refer to three-dimensional particle shapes in which at least two different cross sections taken through said particle have different shapes.

[0026] In particular, the lightweight aggregates meet the requirements for lightweight aggregates as defined in DIN EN 13055:2016.

[0027] In particular, the mortar composition is a dry mortar composition, which means that the mortar composition is essentially free of water or the amount of water is less than 1% by weight, in particular less than 0.5% by weight or less than 0.1% by weight, based on the total weight of the mortar composition.

[0028] According to a preferred embodiment, the mortar composition is a one-component mixture, which means that all the individual materials and / or substances are mixed together. One-component compositions are particularly easy to handle and eliminate the risk of the user mixing up or incorrectly dosing the individual components.

[0029] However, it is possible in principle to provide a two-component mortar composition, or even a multi-component mortar composition. The first component may be present in a first container, for example, containing a hydraulic binder and a polymer. The second component, present in a second container, may contain an aggregate. Other distributions are possible as well. A two-component or multi-component mortar composition, for example, makes it possible to tailor the mortar composition for a specific application.

[0030] The preferred amount of hydraulic binder is 15-45% by weight, in particular 20-40% by weight, especially 25-35% by weight, based on the total weight of the mortar composition in the dry state.

[0031] Preferably, the hydraulic binder comprises or consists of portland cement, aluminate cement, sulfoaluminate cement, latent hydraulic material and / or pozzolanic binder material, calcium sulfate hemihydrate, anhydrite and / or hydrated lime.

[0032] Preferred Portland cements are those according to standard EN 197, in particular of type CEM I. The term "aluminous cement" in particular denotes a cement with an aluminium content, measured as Al2O3, of at least 30% by weight, in particular at least 35% by weight, in particular between 35 and 58% by weight. Preferably, the aluminous cement is an aluminous cement according to standard EN 14647. Preferably, the sulfoaluminate cement is a calcium sulfoaluminate cement.

[0033] The term "latent hydraulic material and / or pozzolanic binder material" in particular denotes a type II concrete additive having latent hydraulic and / or pozzolanic properties according to EN 206-1. In particular, the latent hydraulic material or pozzolanic binder material comprises or consists of slag, fly ash, silica fume, metakaolin and / or natural pozzolans. In that respect, slag and / or fly ash, in particular furnace slag, are particularly preferred.

[0034] Calcium sulfate hemihydrate, i.e. CaSO4·0.5H2O, can exist as α-hemihydrate or β-hemihydrate. Anhydrite is in particular anhydrite II and / or anhydrite III, while hydrated lime refers to calcium hydroxide.

[0035] Particularly preferred hydraulic binders comprise aluminate cement and / or sulfoaluminate cement, preferably in a proportion of 1 to 15% by weight, in particular 2 to 12% by weight, in particular 5 to 10% by weight, based on the total weight of the mortar composition in the dry state.

[0036] In particular, the hydraulic binder preferably comprises Portland cement in a proportion of 10 to 30% by weight, in particular 15 to 25% by weight, especially 16 to 20% by weight, relative to the total weight of the mortar composition in the dry state.

[0037] In particular, the hydraulic binder comprises Portland cement and aluminate cement and / or sulfoaluminate cement in a weight ratio of Portland cement to aluminate cement and / or sulfoaluminate cement of 1 to 5, in particular 1.6 to 4, in particular 2 to 3.5.

[0038] In particular, the hydraulic binder comprises latent hydraulic materials and / or pozzolanic binder materials, in particular slag and / or fly ash, preferably in a proportion of 1 to 15% by weight, in particular 2 to 12% by weight, in particular 5 to 10% by weight, based on the total weight of the mortar composition in the dry state.

[0039] In particular, the hydraulic binder comprises an aluminate cement and / or a sulfoaluminate cement and a latent hydraulic material and / or a pozzolanic binder material in a weight ratio of aluminate cement and / or a sulfoaluminate cement to latent hydraulic material and / or a pozzolanic binder material of 0.5 to 3, in particular 0.7 to 2.5, in particular 1 to 2.

[0040] In particular the hydraulic binder comprises Portland cement and latent hydraulic material and / or pozzolanic binder material in a weight ratio of Portland cement to latent hydraulic material and / or pozzolanic binder material of 10 to 1, in particular 7 to 1.5, especially 5 to 3.

[0041] Preferably, the hydraulic binder is - 10-30% by weight, in particular 15-25% by weight, especially 16-20% by weight of Portland cement; - optionally 1 to 15% by weight, in particular 2 to 12% by weight, in particular 5 to 10% by weight, of aluminate cement and / or sulfoaluminate cement; - optionally 1 to 15% by weight, in particular 2 to 12% by weight, in particular 5 to 10% by weight, of latent hydraulic and / or pozzolanic binder materials, in particular slag and / or fly ash; - optionally 0.5 to 8% by weight, in particular 1 to 6% by weight, in particular 2 to 4% by weight, of calcium sulfate hemihydrate and / or anhydrite; - optionally 0.1 to 5% by weight, in particular 0.2 to 3% by weight, in particular 0.5 to 1.5% by weight, of hydrated lime Including, All amounts herein are based on the total weight of the mortar composition in its dry state.

[0042] Regarding the lightweight aggregate, the particle density of the lightweight aggregate is preferably 100 to 2,000 kg / m 3 , especially 400~1,900kg / m 3 , preferably 700 to 1,500 kg / m 3 Or 800~1,300kg / m 3 It is.

[0043] In particular, the proportion of lightweight aggregate is between 7 and 30% by weight, in particular between 9 and 25% by weight, in particular between 10 and 20% by weight, relative to the total weight of the mortar composition in the dry state.

[0044] The lightweight aggregate may, for example, comprise or consist of cork, wood, rubber, plastic and / or porous particles.

[0045] According to a preferred embodiment, the lightweight aggregate consists of inorganic particles. In particular, the lightweight aggregate does not contain any cork, wood, plastic or rubber aggregate. This helps to improve the fire resistance of the mortar composition.

[0046] Preferably, the particle size of the lightweight aggregate is 0.01 to 2 mm, especially 0.02 to 1.5 mm, preferably 0.05 to 1.0 mm, especially 0.08 to 0.5 mm or 0.09 to 0.3 mm.

[0047] In this context, particle size can be measured by laser diffraction as described in ISO 13320:2009. Preferably, the particle size of non-spherical or irregular particles is expressed as the equivalent spherical diameter of a sphere of equivalent volume. In particular, the lower value of the range indicated for particle size represents the D1 value, while the upper value of the range indicated for particle size represents the D99 value. In other words, in this case, 1% of the particles have a particle size smaller than the lower value of the range, while 1% of the particles have a particle size larger than the upper value of the range.

[0048] A preferred lightweight aggregate comprises or consists of lamellar particles and / or porous particles. In particular the lightweight aggregate is selected from porous particles. The term "lamellar particles" refers in particular to materials with a lamellar crystal structure. In particular, lamellar materials are plate-like materials. Plate-like materials are in particular materials whose length and width are greater than their thickness.

[0049] Thus, in a further preferred embodiment, the lightweight aggregate of the mortar composition comprises or consists of porous particles, in particular having a porosity of at least 25% by volume, in particular at least 50% by volume, in particular at least 75% by volume, relative to the total volume of the porous particles.

[0050] In particular, the porous particles are selected from expanded silica, volcanic rocks such as pumice and / or perlite. Expanded silica or expanded glass are highly preferred.

[0051] Particularly preferred lightweight aggregates comprise or consist of porous inorganic particles, especially expanded silica.

[0052] If present, the layered material is preferably selected from clays and / or micas. In the context of the present invention, "clay" denotes in particular phyllosilicates and / or sheet silicates. Particularly preferred layered materials comprise or consist of vermiculite.

[0053] According to a preferred embodiment, the mortar composition comprises 7 to 22% by weight, in particular 10 to 20% by weight, especially 12 to 20% by weight, of further aggregates, based on the dry weight of the mortar composition.

[0054] In particular, the particle density of the further aggregate is at least 100 kg / m greater than the particle density of the light aggregate. 3 , in particular at least 250 kg / m 3 , preferably at least 500 kg / m 3 expensive.

[0055] In particular, the further aggregate is 2,000 kg / m 3 More specifically, 2,100 kg / m 3 Over 2,200kg / m 3 It has a particle density of .

[0056] The particle size of the further aggregates is preferably 0.01 to 2 mm, in particular 0.02 to 1.5 mm, preferably 0.05 to 1.0 mm, in particular 0.08 to 0.3 mm or 0.1 to 0.2 mm.

[0057] In particular, the further aggregates include sand, quartz, calcium carbonate, natural river sand, gravel, basalt and / or metal aggregates, especially sand and / or calcium carbonate.

[0058] In particular, the weight ratio of the lightweight aggregate to the further aggregate is 0.1 to 5, in particular 0.4 to 2.5, in particular 0.5 to 1.8, preferably 0.6 to 1.3 or 0.7 to 1.1.

[0059] In particular, the particle density of lightweight aggregate is 400 to 1,900 kg / m 3 , preferably 700 to 1,500 kg / m 3 Or 800~1,300kg / m 3 and the further aggregate is 2,000 kg / m 3 It has a particle density of .

[0060] In particular, the particle density of lightweight aggregate is 700 to 1,500 kg / m 3 and the further aggregate is 2,100 kg / m 3 It has a particle density of .

[0061] Preferably, the lightweight aggregate comprises or consists of cork, wood, rubber, plastic and / or porous particles, further aggregates include sand, quartz, calcium carbonate, natural river sand, gravel, basalt and / or metal aggregates, especially sand and / or calcium carbonate.

[0062] A preferred amount of the at least one polymer is from 15 to 45% by weight, in particular from 20 to 40% by weight, especially from 25 to 37% by weight, relative to the total weight of the mortar composition.

[0063] Preferably, at least one polymer used in the mortar composition is a water-soluble or water-redispersible polymer, especially a water-redispersible polymer. Such polymers have proven to be useful in the present mortar composition. However, other polymers may be suitable as well, for example for specific purposes.

[0064] Preferably, the at least one polymer is present in a solid state, especially as a powder.

[0065] Preferably, at least one polymer has a glass transition temperature of -45 to 10°C, in particular -35 to 5°C, preferably -25 to 0°C, in particular -20 to 0°C, particularly preferably -20 to -10°C. Such polymers can further improve the strength and noise suppression properties of the mortar composition. Redispersible polymers of these glass transition temperatures are most preferred.

[0066] The glass transition temperature is measured by differential scanning calorimetry according to standard ASTM E1356-08(2014).

[0067] In particular, at least one polymer is a homopolymer or copolymer based on one or more monomers selected from vinyl esters, vinyl acetate, vinyl alcohol, vinyl chloride, vinyl laurate, acrylic acid, acrylates, methacrylic acid, methacrylates, methyl methacrylate, acrylonitrile, styrene, butadiene, ethylene, or mixtures thereof.

[0068] Copolymers based on vinyl esters, ethylene, styrene and / or acrylic esters, especially copolymers of vinyl acetate and ethylene and / or copolymers of acrylic esters and styrene, are highly preferred.

[0069] Preferably, the polymer is selected from poly(vinyl acetate-ethylene), poly(vinyl acetate-ethylene-methyl methacrylate), poly(vinyl acetate-ethylene-vinyl ester), poly(vinyl acetate-ethylene-acrylic ester), poly(vinyl acetate-ethylene-vinyl laurate), poly(vinyl acetate-vinyl versatate), poly(acrylate-acetonitrile), poly(acrylate-styrene butadiene) or mixtures thereof. Poly(vinyl acetate-ethylene) and / or poly(acrylate-styrene) are highly preferred as polymers.

[0070] However, other polymers could be suitable as well.

[0071] According to a preferred embodiment, the polymer comprises two different copolymers, in particular a copolymer of vinyl acetate and ethylene and a copolymer of an acrylic ester and styrene. In that respect, the ratio of the two different copolymers is preferably 0.5 to 10:1, preferably 1 to 5:1, in particular 2.5 to 4:1. In other words, the polymer is preferably present in the form of a mixture of two copolymers, in particular a first copolymer of vinyl acetate and ethylene and a second copolymer of an acrylic ester and styrene. In this case, the mortar composition therefore comprises two different copolymers.

[0072] After all, such types of polymer mixtures are very beneficial in this connection, since they serve to strongly improve the flexibility of the composition, in particular the flexibility 24 h after the preparation of the mortar composition.

[0073] In particular, the weight ratio of the at least one polymer to the lightweight aggregate is between 0.5 and 10, in particular between 1 and 5, especially between 1.2 and 3.5 or between 1.7 and 2.5.

[0074] Preferably, the weight ratio of the at least one polymer to the hydraulic binder in the mortar composition is between 0.1 and 17, in particular between 0.2 and 7, especially between 0.3 and 5, in particular between 0.4 and 2 or between 0.7 and 1.5. This is especially true when the weight ratio of the polymer to the lightweight aggregate is between 0.5 and 10, in particular between 1 and 5, in particular between 1.2 and 3.5 or between 1.7 and 2.5.

[0075] In particular, the weight ratio of the at least one polymer to the Portland cement in the mortar composition is between 0.25 and 7, in particular between 0.75 and 5, in particular between 0.9 and 4, in particular between 1 and 3 or between 1.2 and 2. This is especially true when the weight ratio of the polymer to the lightweight aggregate is between 0.5 and 10, in particular between 1 and 5, in particular between 1.2 and 3.5 or between 1.7 and 2.5.

[0076] Furthermore, it can be beneficial if the mortar composition comprises at least one additive selected from the group consisting of set time regulators, plasticizers, defoamers, rheology modifiers, thixotropic agents, aeration and / or foaming agents, shrinkage inhibitors, corrosion inhibitors, fire retardants, fibers, and chromium reducers.

[0077] Preferably, the proportion of additives in total is 0 to 10% by weight, in particular 1 to 10% by weight, relative to the weight of the mortar composition in the dry state.

[0078] In particular, the mortar composition comprises a rheology modifier, the proportion of which is preferably 0.001 to 1% by weight, in particular 0.2 to 0.5% by weight, based on the weight of the mortar composition in the dry state.

[0079] According to another preferred embodiment, the mortar composition comprises a plasticizer, which is in particular selected from the group consisting of lignosulfonates, gluconates, naphthalenesulfonates, melaminesulfonates, vinyl copolymers and / or polycarboxylate ethers. Polycarboxylate ethers are preferred. In particular, the plasticizer is chemically different from the abovementioned polymers and rubbers. The proportion of polycarboxylate ethers is preferably between 0.001 and 1% by weight, in particular between 0.05 and 0.1% by weight, relative to the weight of the mortar composition in the dry state.

[0080] Preferably, the mortar composition comprises fibers, in particular glass fibers, plastic fibers and / or cellulose fibers. Glass fibers and / or plastic fibers are very preferred. Highly preferred plastic fibers are polyalkylene fibers, for example polyethylene fibers.

[0081] The proportion of the fibers is preferably 0.001 to 3% by weight, in particular 0.01 to 2.0% by weight, and especially 0.1 to 1% by weight, based on the weight of the mortar composition in the dry state.

[0082] In general, the preferred length of the fibers is 0.05 to 12 mm, particularly 0.05 to 5 mm. The diameter of the fibers is, for example, 0.5 to 1,000 μm, particularly 1 to 100 μm, and especially 5 to 40 μm.

[0083] The preferred length of the glass fibers is 0.5 to 12 mm, particularly 2 to 5 mm. The fiber diameter is, for example, 0.5 to 1,000 μm, particularly 1 to 100 μm, and especially 5 to 40 μm.

[0084] The preferred length of the plastic fibers is 0.05 to 2 mm, particularly 0.1 to 0.5 mm. The diameter of the plastic fibers is, for example, 0.5 to 1,000 μm, particularly 1 to 100 μm, and particularly 5 to 40 μm.

[0085] The proportion of the flame retardant is selected from 0 to 5% by weight, based on the total weight of the mortar composition in the dry state. The flame retardant can be selected, for example, from the list consisting of inorganic substances, in particular aluminum hydroxide, aluminum sulfate, borates, magnesium hydroxide, ammonium sulfate, expanded graphite (expanded graphite) and red phosphorus. However, it is also possible to use organic halogen compounds and / or organic phosphorus compounds in addition to or instead of the inorganic substances.

[0086] A preferred mortar composition is - 16-20% by weight of Portland cement; - optionally 5 to 10% by weight of aluminate cement and / or sulfoaluminate cement; - optionally 5 to 10% by weight of a latent hydraulic material and / or a pozzolanic binder material, in particular slag; - 10-20% by weight of lightweight aggregates in the form of porous inorganic particles, in particular foamed glass, preferably with a particle size of 0.08-0.5 mm; - 10-20% by weight of further aggregates, in particular sand and / or quartz, preferably with a particle size of 0.08-0.3 mm; - 25 to 40% by weight of a polymer with a glass transition temperature of -20 to 45°C, where preferably the polymer is a copolymer of vinyl acetate and ethylene and / or a copolymer of acrylic esters and styrene, comprising or consisting essentially of All amounts herein are based on the total weight of the mortar composition in dry form.

[0087] A highly preferred mortar composition is - 16-20% by weight of Portland cement; - 5 to 10% by weight of aluminate cement and / or sulfoaluminate cement; - optionally 5 to 10% by weight of a latent hydraulic material and / or a pozzolanic binder material, in particular slag; - 10-20% by weight of lightweight aggregate in the form of foamed glass, preferably with a particle size of 0.08-0.5 mm; - 10-20% by weight of further aggregates in the form of sand and / or quartz, preferably with a particle size of 0.08-0.3 mm; - 25 to 37% by weight of a polymer with a glass transition temperature of -20 to 0°C (wherein the polymer is preferably a copolymer of vinyl acetate and ethylene and / or a copolymer of acrylic esters and styrene); comprising or consisting essentially of wherein the weight ratio of polymer to lightweight aggregate is preferably between 1 and 5, in particular between 1.2 and 3.5 or between 1.7 and 2.5; wherein the weight ratio of lightweight aggregate to further aggregate is preferably between 0.4 and 2.5, in particular between 0.5 and 1.8, preferably between 0.6 and 1.3 or between 0.7 and 1.1; All amounts herein are based on the total weight of the mortar composition in dry form.

[0088] Another aspect of the invention relates to a method for producing a workable mortar composition comprising the step of adding water to a mortar composition as described above.

[0089] In this respect, preferably the weight ratio of water to the mortar composition in the dry state is between 0.20 and 0.50, in particular between 0.22 and 0.40, especially between 0.23 and 0.34 or between 0.24 and 0.30.

[0090] Another preferred range of the water to dry mortar composition ratio is 0.20-0.25. If the ratio is kept in the range of 0.20-0.25, a non-drip composition is obtained, which is very beneficial for vertical applications.

[0091] A range of water to dry mortar composition ratios of 0.27 to 0.50 is also preferred, which results in a self-leveling composition, which is useful, for example, for horizontal applications, such as floor finishes.

[0092] A further aspect of the invention is a hardened mortar composition obtained by adding water to a mortar composition as described above or by a method as described above. Preferably, the mortar composition is placed on a substrate, in particular on a floor, especially made of metal and / or concrete.

[0093] Preferably, the hardened mortar composition is in the form of a layer, coating and / or sheet, especially applied onto a substrate. Preferably, the hardened mortar composition has a thickness of 0.5 to 20 mm, especially 1 to 10 mm, preferably 1 to 5 mm.

[0094] Another aspect of the invention relates to a moulded body, in particular a flat layer, comprising a hardened mortar composition, the hardened mortar composition being a mortar composition as defined above after hardening with water, or in other words, the hardened mortar composition being obtained by mixing water with a mortar composition as defined above.

[0095] In particular, the shaped bodies are characterized by viscoelastic properties, meaning that they exhibit a phase lag between strain and corresponding stress that results in the ability to simultaneously store and dissipate energy, in contrast to, for example, elastic bodies, where stress and strain remain in phase.

[0096] In particular, the shaped body is a flat layer, in particular with a thickness of 0.5 to 10 mm, preferably 1 to 5 mm. In this context, a flat layer is in particular an object whose width and length are greater than its thickness.

[0097] Moulded bodies with the above mentioned properties are particularly suitable for viscoelastic structures or acoustic damping elements.

[0098] A further aspect of the invention relates to a structure, in particular a floor, wall or ceiling, comprising the above-mentioned molding. Preferably, a support element and / or a cover element is attached to the molding. The cover element can be, for example, a containment layer.

[0099] In particular the structure is a deck structure of a ship or offshore facility.

[0100] In particular, the shaped body is arranged between the support element and the cover element, in which case the shaped body is constrained between the support element and the cover element.

[0101] In particular, the support element is a metal layer, in particular made of steel and / or aluminum.A preferred cover element is formed as a flat layer.

[0102] In particular, the cover element is a cement-based layer, for example a mortar layer, and / or a metal-based layer. If the cover element is a cement-based layer, the cement-based layer is chemically different from the shaped body and / or the mortar composition of the invention.

[0103] In another preferred embodiment, the covering element is a metal-based layer, in particular comprising or consisting of metal sheets and / or tiles. Preferably, the coverage of the covering element is at least 50%, in particular at least 75% or at least 90%, relative to the area covered by the shaped body.

[0104] In a further preferred embodiment, the cover element may be covered with at least one further layer, such as an insulating layer and / or a further functional covering.

[0105] Optionally, it is possible to have a primer between the support element and the molded body, which could further increase adhesion between the support element and the molded body, and a primer can be present between the molded body and the cover element.

[0106] Preferably, the structure, especially the deck structure of a ship or offshore facility, is - metal support elements, in particular metal decks, preferably made of steel and / or aluminium; - mouldings as described above, in particular with a thickness of 0.5 to 10 mm, preferably 1 to 5 mm; - covering elements, in particular metal covering elements, such as metal tiles and / or plates (wherein the coverage of the covering elements is preferably at least 75%, in particular at least 90%); - optionally an insulating layer, in particular made of mineral wool; - Optionally, a deck covering It comprises or consists of:

[0107] However, other structures can be produced similarly.

[0108] In particular, "mineral wool" refers to any fibrous material formed by spinning or drawing molten mineral or rock material, such as stone, glass, slag and / or ceramics. In particular, mineral wool is present in the form of a fabric, which preferably consists of fibrous material consisting of at least 75% by weight, preferably to the extent of at least 90% or 95% by weight, of stone, glass, slag and / or ceramics.

[0109] Particularly preferred, the insulating layer comprises or consists of stone wool, slag wool and / or glass wool.

[0110] According to another preferred embodiment, the structure comprises: - the body of the vehicle, in particular the bodywork (wherein preferably the body is essentially made of metal, plastic and / or composite material), in particular the metal being selected from steel and / or aluminium and / or the composite material being selected from fibre composite materials, such as for example carbon fibre reinforced polymer and / or glass fibre reinforced polymer; - optionally at least one intermediate layer, in particular with a thickness of 0.5 to 1,000 μm, in particular 1 to 500 μm or 5 to 100 μm. In particular, the intermediate layer is selected from a primer, a paint and / or a coating. In particular, the intermediate layer comprises or essentially consists of an electrophoretic deposition layer, in particular when the body comprises or essentially consists of a metal. In particular, the intermediate layer is an intermediate layer deposited by electrocoating, cathodic electrodeposition, anodic electrodeposition, electrophoretic coating, electrophoretic painting and / or cathodic dip paint coating (KTL). In particular, the intermediate layer is deposited by cathodic dip paint coating. In particular, cathodic dip paint coating is a coating based on polymers, in particular epoxy polymers and / or (meth)acrylic polymers. Cathodic dip paint coating typically ensures an effective and long-lasting corrosion protection with high temperature and chemical resistance. In addition, it is scratch-resistant and protects against stone chips); - a shaped body as described above, in particular with a thickness of 0.5 to 10 mm, preferably 1 to 5 mm, attached to the body and / or intermediate layer of the vehicle; It comprises or consists of:

[0111] It is therefore possible to attach the shaped body, which may optionally be coated with at least one intermediate layer, to the body of a vehicle in order to reduce noise and vibration and / or to produce a fire barrier in the body of the vehicle.

[0112] In this case, in particular, the molded body can be essentially uncovered. In other words, in this case, the molded body does not include any cover element. However, for specific purposes, it is also possible to add a cover element on top of the molded body.

[0113] Such structures, including the vehicle body, are particularly lightweight and can be manufactured in a very efficient manner, as described in more detail below, making them highly suitable for electric vehicles, and particularly electric automobiles.

[0114] Another aspect of the invention relates to a method for producing a structure, in which the mortar composition of the invention is mixed with water, applied onto a support structure and covered with a cover element, in which the support structure and the cover element are defined as described above, in particular the mortar composition is applied with a thickness of 0.5 to 10 mm, in particular 1 to 5 mm.

[0115] According to a preferred embodiment, the support element used in the method is a metal layer, in particular made of steel and / or aluminum. A preferred cover element is formed as a flat layer. In particular, the cover element is a cement-based layer, for example a mortar layer, and / or a metal-based layer, for example comprising or consisting of metal sheets and / or tiles.

[0116] In another method for producing structures, including in particular vehicle bodies, the mortar composition of the present invention is mixed with water to obtain a processable composition and applied onto a supporting structure, in particular a vehicle body, in particular a car body, in which case, preferably, the processable composition is sprayed onto the supporting structure, in particular the vehicle body.

[0117] Preferably, the vehicle body comprises an intermediate layer, in particular with a thickness of 0.5 to 1,000 μm, in particular 1 to 500 μm or 5 to 100 μm. In particular, the intermediate layer is selected from a primer, a paint and / or a coating as described above. In particular, the intermediate layer is a cathodic dip paint coating (KTL). In particular, the cathodic dip paint coating is a coating based on a polymer, in particular an epoxy polymer and / or a (meth)acrylic polymer.

[0118] Thus, in an exemplary method, the body of a vehicle, in particular a car body, is treated with a cathodic dip paint coating, after which the processable mortar composition of the present invention is applied onto the cathodic dip paint coating and / or onto a further intermediate layer.

[0119] In particular, the workable mortar composition is applied onto specifically selected areas of the body of a vehicle to achieve vibration and / or noise reduction and / or to construct a fire barrier.

[0120] In particular, the processable mortar composition is applied onto the vehicle body in the form of one, two, three, four, five or even more strips, circles, polygons and / or complex shapes. In particular, the mortar composition is applied with an essentially constant thickness and / or with a non-constant thickness.

[0121] Highly preferred processable mortar compositions are applied by automated application systems, especially with manipulators capable of moving the discharge spray nozzle in at least one, preferably at least two, especially preferred at least three dimensions. Highly preferred processable mortar compositions are applied by robotic arms.

[0122] This is particularly preferred in vehicle bodies with complex structures, such as car bodies, since the manipulator can easily reach areas that are difficult to access and can accurately follow uneven surfaces. In addition, the method of the present invention does not require the manufacture of prefabricated damping elements, which have to be installed later. Therefore, there is no need to keep prefabricated damping elements in stock. Rather, the damping elements can be manufactured directly. With the method of the present invention, it is even possible to apply the mortar composition in different vehicle bodies using one and the same manipulator. All that needs to be changed each time the vehicle body is the computer program that controls the manipulator. Hence, the method of the present invention is very flexible, fast and efficient.

[0123] Overall, with the method of the invention it is possible to obtain a vehicle body, in particular a car body, with good acoustic and vibration damping properties, in that the part of the vehicle body that is uniformly covered with the mortar composition of the invention can act as a particularly favorable fire barrier in electric vehicles.

[0124] A further aspect of the present invention relates to the use of the mortar composition and the molded body as described herein. Particularly preferred, the mortar composition and / or the molded body are used on structural elements, floors, walls and / or ceilings, preferably on floors.

[0125] In particular the mortar compositions and / or shaped bodies are used for sound attenuation, in particular in vehicles, buildings and / or offshore installations, in particular in motor vehicles or in ships.

[0126] The mortar compositions and / or moldings can also be used in fire protection systems, especially as fire walls and / or fire barriers, as fire-resistant coatings and / or barriers, in particular in vehicles, buildings and / or offshore facilities, especially in motor vehicles or in ships.

[0127] In particular, the mortar compositions and / or moldings are used in combination for sound attenuation, in particular as fire walls and / or fire barriers in fire protection systems, in particular in vehicles, buildings and / or offshore installations, in particular in motor vehicles or on ships.

[0128] Furthermore, the mortar composition and / or the shaped body can be used as an underlayment and / or primer for covering elements on supporting structures.

[0129] Further preferably, the mortar composition and / or the molding are used to increase the adhesion between the support structure and the cover element, whereby the cover element is preferably a mortar layer and / or a metal-based layer and the support structure is preferably a metal layer, in particular made of steel and / or aluminum.

[0130] Further advantageous configurations of the invention are evident from the exemplary embodiments.

[0131] The drawings used to explain the embodiments are shown below. [Brief description of the drawings]

[0132] [Figure 1] It shows a schematic cross-section of the test setup in which the acoustic measurements were performed. The setup comprises two reverberation chambers (1, 3) with a common opening for the receiving test deck (2). [Diagram 2] A perspective view of a test deck (2) equipped with a vibration exciter (4) is shown. [Diagram 3] A cross section of a floor structure on a steel deck (4) is shown. The floor structure comprises a hardened mortar composition (5) covered with a steel plate (6). [Figure 4] Shown is a cross section of another floor structure on a steel deck (7). The floor structure comprises a hardened mortar composition (8) covered by a steel plate (9) and a floating floor (10, 11) on top. [Diagram 5] Shown is a cross-section of the setup used for the combustion tests, which includes a furnace (12) covered by a steel deck (13), on top of which floor structures (14, 15, 16, 17) are applied. [Figure 6] Measured sound transmission loss R is shown for the mortar composition (filled circles) as well as the bare steel deck (open circles).

[0133] As a rule, identical parts are provided with the same reference numbers in the figures. EXAMPLES

[0134] 1. Mortar composition Table 1 shows three mortar compositions M1 to M3. The mortar compositions were prepared by mixing all of the components in a dry state. Mortar compositions M1 to M3 exist as dry powders.

[0135] [Table 1]

[0136] Mortar compositions M1-M2 were mixed with water (weight ratio of water to total weight of dry mortar composition=0.29) to obtain workable compositions.

[0137] 2. Processing characteristics The flow spread values ​​were evaluated according to standard EN 12350-5:2009. Values ​​in the range of 176 mm (composition M1) and 173 mm (composition M2) were obtained immediately after preparation. The mortar compositions therefore exhibit flow behavior that facilitates processing.

[0138] 3.Adhesive properties Mortar compositions M1 and M2 were applied to a thickness of 2 mm on a cleaned flat steel plate.

[0139] For comparative reasons, a similar system was prepared using 2 mm of SikaFloor® Marine PU-Red (polyurethane-based layer) instead of mortar composition M1.

[0140] Adhesion tests carried out similar to standard EN 1348:2007 on mortar compositions on steel substrates showed - 0.8 MPa for composition M1 and 1.3 MPa for composition M2 after 7 days; - 1.0 MPa for composition M1 and 1.3 MPa for composition M2 after 28 days; - 0.9 MPa for the comparative composition after 7 days and after 28 days The adhesive strength was .

[0141] Thus, in terms of adhesion to steel, the mortar composition of the present invention can be compared to polyurethane-based systems.

[0142] 4. Acoustic characteristics 4.1 Test facility The measurements were carried out in two reverberation rooms as shown in Figure 1. The rooms are built on two separate foundations made of 30 cm thick concrete. Between the source room 1 and the receiving room 3 there is an opening of 2.99 m x 3.37 m, in which the test deck 2 is installed, i.e. in the ceiling of the source room 1 and in the floor of the receiving room 3. The volumes of the source room 1 and the receiving room 3 are respectively 243 m 3 and 230m 3 It is.

[0143] Excitation of the test deck 2 with airborne and impulsive noise is performed with loudspeakers and a tapping machine as described in standard ISO 10140:2010.

[0144] Excitation of the test deck 2 with structure-borne noise is performed by a vibration exciter 4 coupled to a steel plate 5, which is mounted perpendicular to and below the steel deck located in the opening, as shown in Figure 2. With this arrangement, a reverberant vibration field is established both in the steel plate coupled to the vibration exciter and in the steel deck simulating the real conditions occurring in ship structures.

[0145] 4.2 Measurements according to ISO 10140:2010 Measurements according to ISO 10140:2010 were performed as follows: During airborne and structure-borne acoustic measurements, excitation is provided by broadband pink noise in the frequency range 20-10000 Hz.

[0146] The response, ie sound pressure level in the receiving room 3 for airborne and impact sound insulation measurements, or velocity level on the floor for structure-borne sound measurements, is measured in ⅓ octave filter bands with centre frequencies between 50 Hz and 5000 Hz.

[0147] Measurements in the 1 / 3 octave filter bands of 50 Hz, 63 Hz and 80 Hz are not required according to ISO 10140:2010. However, based on experience from previous measurements on board ships, it seems reasonable to include these frequency ranges.

[0148] All relevant equipment in the test setup will be calibrated prior to or during the test period for every structure.

[0149] 4.3 Measurement according to ASTM E2963-16 The reference deck must not be removed from the test opening during the measurement series. This is necessary in order not to introduce installation differences in the test fixture.

[0150] Transmission loss and acceptance measurements are performed simultaneously with airborne noise excitation in the source room. Sound absorption measurements are performed in conjunction with the transmission loss measurements. Transmission loss measurements are performed in accordance with ASTM E90-09.

[0151] First, the damping properties for the restrained damped test structures were measured in terms of loss factor using the test beam method as described, for example, in ASTM E756-5 (2010).

[0152] All calculations are performed for each 1 / 3 octave band.

[0153] 4.4 Test Deck Example 1: The floor is a restrained damping structure on a steel deck 4 as shown in Figure 3. The restrained damping structure consists of a 1 mm viscoelastic damping layer 5 of mortar composition M2. The density of the compound (molding material) is 1,300 kg / m 3 On top of the damping layer a 1.5 mm steel plate 6 is applied with a coverage of 90%. The total surface mass is approximately 11.9 kg / m for the whole structure. 2 The total building height is 2.5~3mm.

[0154] Example 2: In Example 2, a constrained damping structure consisting of a 3 mm viscoelastic damping layer of mortar composition M2 was used. The set-up was otherwise identical to Example 1.

[0155] Example 3: The floor is a combined restrained damping and floating floor structure on a steel deck 7 as shown in Figure 4. The restrained damping structure consists of an approximately 1.5 mm viscoelastic damping layer 8 of mortar composition M2. The density of the compound (molding material) is 1,300 kg / m 3 On top of the damping layer a 1.5 mm steel plate 9 with 90% coverage is applied.

[0156] On top, 140kg / m 3 A floating floor is applied consisting of 50 mm of mineral wool 10 (type SeaRox SL 436) with a density of 1000 mm. The top layer 11 consists of 25 mm of Litosilo X. The total surface mass is approximately 45.9 kg / m for the whole structure. 2 The total building height is 78mm.

[0157] Example 4: For comparative reasons, a confined damping structure consisting of 1 mm SikaFloor® Marine PU-Red (polyurethane-based layer) was used instead of the mortar composition M2 in Example 4. Otherwise, the set-up was essentially identical to Example 1.

[0158] 4.5 Results For illustration, Figure 6 shows the measured sound transmission loss R (filled circles) for the mortar composition M2 of Example 1, expressed in dB per 1 / 3 octave frequency band. For comparison, the results of measurements on an uncovered steel deck (open circles) are also shown. The difference between the curves for the test deck and the control steel deck therefore indicates the improvement in sound reduction and impact sound insulation due to the applied floor structure.

[0159] Table 2 shows a summary of the measured specific properties for the three examples.

[0160] [Table 2]

[0161] Thus, all of the tested compositions 1 to 3 clearly show significant noise and vibration suppression, at least comparable to the standard PU-based system (Example 4). Thus, the mortar compositions according to the invention can be used as replacements for known polyurethane systems.

[0162] 5.Fire resistance As depicted in Figure 5, the thickness of 8 mm and the thickness of 10 m 2 The combustion tests were carried out in a furnace 12 covered with a steel deck 13 of an area of ​​about 1 mm. The steel deck 12 was covered with a layer 14 of mortar composition M2 of about 1 mm. On top of the layer 14 a steel plate 15 of about 90% coverage as well as insulation 16 and deck covering 17 were applied.

[0163] The fire tests were conducted in accordance with the International Code for the Application of Fire Test Procedures, 2010 (International Maritime Organization, Resolution MSC.307(88) adopted on 3 December 2010).

[0164] Tests showed that the setup prevented the passage of flame and smoke for 60 minutes. The average temperature rise for the non-exposed deck side was less than 140° C. above the temperature before the start of the standard fire test. Overall, with the mortar composition of the present invention it is possible to manufacture class A-60 type decks.

[0165] In summary, the mortar composition of the present invention can be used to prepare an effective fire barrier.

[0166] Therefore, the mortar composition according to the invention can indeed be used as an improved replacement for known polyurethane systems.

[0167] It will therefore be appreciated by those skilled in the art that the present invention can be embodied in other specific forms without departing from its spirit or essential characteristics. The presently disclosed embodiments are therefore considered in all respects to be illustrative and not restrictive. The present disclosure includes the following aspects. <Aspect 1> Mortar compositions, in particular for preparing viscoelastic structures and / or fire barriers, comprising or consisting of: (a) 15 to 50 weight percent of a hydraulic binder; (b) 5 to 35% by weight of lightweight aggregate; (c) 5 to 25% by weight of a further aggregate having a particle density higher than the particle density of the lightweight aggregate; (d) 10 to 50 weight percent of at least one polymer. <Aspect 2> 2. The mortar composition according to embodiment 1, wherein the hydraulic binder comprises Portland cement and aluminate cement and / or sulfoaluminate in a weight ratio of Portland cement to aluminate cement and / or sulfoaluminate of 1 to 5, particularly 1.6 to 4, in particular 2 to 3.5. <Aspect 3> The particle density of the lightweight aggregate is 100 to 2,000 kg / m 3 , especially 400~1,900kg / m 3 , preferably 700 to 1,500 kg / m 3 Or 800~1,300kg / m 3 and the further aggregate is 2,000 kg / m 3 More specifically, 2,100 kg / m 3 Over 2,200kg / m 3 3. The mortar composition of claim 1 or 2, having a particle density of greater than or equal to 1000 μm. <Aspect 4> 4. The mortar composition according to any one of the preceding claims, wherein the lightweight aggregate comprises or consists of inorganic particles, in particular foamed glass, and wherein preferably the particle size of the lightweight aggregate is 0.01-2 mm, in particular 0.02-1.5 mm, preferably 0.05-1.0 mm, in particular 0.08-0.5 mm or 0.09-0.3 mm. <Aspect 5> 5. The mortar composition according to any one of the preceding aspects, characterized in that the further aggregates are selected from sand, quartz and / or calcium carbonate, wherein preferably the particle size of the further aggregates is 0.01-2 mm, in particular 0.02-1.5 mm, preferably 0.05-1.0 mm, in particular 0.08-0.3 mm or 0.1-0.2 mm. <Aspect 6> A mortar composition according to any one of the preceding aspects, wherein the weight ratio of the lightweight aggregate to the further aggregate is from 0.1 to 5, in particular from 0.4 to 2.5, in particular from 0.5 to 1.8, preferably from 0.6 to 1.3 or from 0.7 to 1.1. <Aspect 7> 7. The mortar composition according to any one of the preceding aspects, characterized in that the polymer is a water-soluble or water-redispersible polymer, especially a copolymer based on vinyl esters, ethylene, styrene, and / or acrylic esters, in particular a copolymer of vinyl acetate and ethylene, and / or a copolymer of acrylic esters and styrene. <Aspect 8> 8. The mortar composition according to any one of the preceding aspects, wherein the polymer comprises two different copolymers, in particular a copolymer of vinyl acetate and ethylene, and a copolymer of an acrylic ester and styrene, wherein preferably the ratio of the two different copolymers is between 0.5 and 10:1, preferably between 1 and 5:1, in particular between 2.5 and 4:1. <Aspect 9> A mortar composition according to any one of the preceding aspects, wherein the weight ratio of said polymer to said lightweight aggregate is from 0.5 to 10, particularly from 1 to 5, and more particularly from 1.2 to 3.5 or from 1.7 to 2.5. <Aspect 10> The mortar composition according to any one of the preceding aspects, comprising or consisting essentially of: - 16-20% by weight of Portland cement; - optionally 5 to 10% by weight of aluminate cement and / or sulfoaluminate cement; - optionally 5 to 10% by weight of a latent hydraulic material and / or a pozzolanic binder material, in particular slag; - 10-20% by weight of lightweight aggregates in the form of porous inorganic particles, in particular foamed glass, preferably with a particle size of 0.08-0.5 mm; - 10-20% by weight of further aggregates, in particular sand and / or quartz, preferably with a particle size of 0.08-0.3 mm; - 25 to 40% by weight of at least one polymer having a glass transition temperature between -20 and 45°C, preferably said polymer being a copolymer of vinyl acetate and ethylene and / or a copolymer of acrylic esters and styrene; All amounts herein are based on the total weight of the mortar composition on a dry basis. <Aspect 11> A molded body, particularly a viscoelastic body, comprising the mortar composition according to any one of embodiments 1 to 10 after hardening with water. <Aspect 12> 12. A structure, in particular a floor, wall or ceiling, comprising a molding according to embodiment 11 and a support element and / or a cover element attached to said molding. <Aspect 13> 13. A structure according to embodiment 12, in particular a deck structure of a ship or offshore facility, comprising or consisting of: - metal support elements, in particular metal decks, preferably made of steel and / or aluminium; - a shaped body according to embodiment 11, in particular with a thickness of 0.5 to 10 mm, preferably 1 to 5 mm; - covering elements, in particular metal covering elements, such as metal tiles and / or plates, preferably the coverage of said covering elements is at least 75%, in particular at least 90%; - optionally an insulating layer, in particular made of mineral wool; - Optionally, a deck covering. <Aspect 14> Use of a mortar composition according to any one of aspects 1 to 10, or of a shaped body according to aspect 11, or of a structure according to aspect 12 or 13 for sound attenuation, in particular in vehicles, buildings and / or offshore installations, especially in automobiles or in ships. <Aspect 15> Use of a mortar composition according to any one of aspects 1 to 10, or of a shaped body according to aspect 11, or of a structure according to aspect 12 or 13 in a fire protection system, in particular as a fire wall and / or fire barrier, as a fire resistant coating and / or barrier.

Claims

1. A deck structure of a ship or offshore facility, - a molding comprising the mortar composition after hardening with water, - a metal support element and a metal cover element attached to said molded body; - an insulating layer made of mineral wool; - Deck cover and Including, The mortar composition is a mortar composition for preparing a viscoelastic structure and / or a fire barrier, (a) 15 to 50% by weight of a hydraulic binder; (b) 5 to 35% by weight of lightweight aggregate; (c) 5 to 25% by weight of a further aggregate having a particle density higher than the particle density of the lightweight aggregate; (d) 10 to 50 weight percent of at least one polymer; Contains or consists of The particle density of the lightweight aggregate is 100 to 2,000 kg / m 3 and the further aggregate has a viscosity of 2,000 kg / m 3 With a particle density of Deck structure.

2. 2. The deck construction of claim 1, wherein the hydraulic binder comprises Portland cement and aluminate cement and / or sulfoaluminate in a weight ratio of Portland cement to aluminate cement and / or sulfoaluminate of 1-5.

3. 3. The deck construction of claim 1 or 2, wherein the lightweight aggregate comprises or consists of inorganic particles.

4. A deck construction as claimed in any one of claims 1 to 3, wherein the further aggregate is selected from sand, quartz and / or calcium carbonate.

5. A deck structure as claimed in any one of claims 1 to 4, wherein the weight ratio of the lightweight aggregate to the further aggregate is from 0.1 to 5.

6. The deck structure according to any one of claims 1 to 5, characterized in that the polymer is a water-soluble or water-redispersible polymer.

7. The deck structure of any one of claims 1 to 6, wherein the polymer comprises two different copolymers.

8. The deck structure according to any one of claims 1 to 7, wherein the weight ratio of the polymer to the lightweight aggregate is from 0.5 to 10.

9. Use of a deck structure according to any one of claims 1 to 8 for acoustic attenuation.

Citation Information

Patent Citations

  • Super-thermal-insulation aerogel foamed concrete and preparation method thereof

    CN107265962A

  • Dry mortar

    EP3348535A1

  • Heat insulating refractory cement

    JP1996059359A

  • Rapid-hardening repair mortar and method of repair using it

    JP2008201643A

  • Lightweight mortar

    JP2009155192A